The effects of polycyclic aromatic hydrocarbons and heavy metals on terrestrial annelids in urban soils - Pižl, Václav; Schlaghamersky, Jiri; Tříska, Jan (Pesquisa Agropecuaria Brasileira, 2010)
The effect of soil contamination by polycyclic aromatic hydrocarbons (PAH) and heavy metals on earthworms and enchytraeids was studied in urban parks, in Brno, Czech Republic. In spring and autumn 2007, annelids were collected and soil samples taken in lawns along transects, at three different distances (1, 5 and 30 m) from streets with heavy traffic. In both seasons, two parks with two transects each were sampled. Earthworms were collected using the electrical octet method. Enchytraeids were extracted by the wet funnel method from soil cores. All collected annelids were counted and identified. Basic chemical parameters and concentrations of 16 PAH, Cd, Cu, Pb, and Zn were analysed from soil from each sampling point. PAH concentrations were rather low, decreasing with the distance from the street in spring but not in autumn. Heavy metal concentrations did not decrease significantly with increasing distance. Annelid densities did not significantly differ between distances, although there was a trend of increase in the number of earthworms with increasing distance. There were no significant correlations between soil content of PAH or heavy metals and earthworm or enchytraeid densities. Earthworm density and biomass were negatively correlated with soil pH; and enchytraeid density was positively correlated with soil phosphorus.